Políticas de alfabetização de surdos adotadas no Brasil (2003 a 2016) e em países da América Latina: diálogos com as orientações da Unesco - Milanezi, Tamille Correia de Miranda (2023)
This text has the general objective of investigating literacy policies for the deaf in Brazil adopted from 2003 to 2016 and in Latin America countries. It presents the following specific objectives; a) to analyse the guidelines coming from the United Nations Educational, Scientific and Cultural Organization (UNESCO) that deal with the educational inclusion of people with diabilities; b) discuss bilingual education and literacy policies for the deaf developed in Brazil and in Latin America countires; c) describe methodologies for teaching sign language and written language in Brazil and in Latin America countries. It starts from the hypothesis that the standardized policies in Brazil in the period from 2003 to 2016 started bilingual educuation for the deaf, triggering significant advances in literacy policies for these subjects. Examines, in a responsive way, national documents, educational policies in Latin America and Unesco world reports referring to the area of deafnes. Its theoretical foundation is studies by Bloch(2001), Le Goff(1990) and Arendt (2002, 2004, 2016) to understand these notions of history and politics. It adopts documentary research, taking Bakhtin( 1987, 2011) as a reference to understand the document as a text. It concludes that knowledge of other realities allows us to perceive the advances in National Education with regard to education and literacy policies for deaf adopted in the period from 2003 to 2016.